A planning approach for sizing the capacity of a port rail system: scenario analysis applied to La Spezia port network. Issue 3 (2016) - Fioribello, S.; Caballini, C.; Sacone, S.; Siri, S.
Abstract: This paper presents an optimization approach for sizing the capacity of port rail networks, in terms of maximum number of trains that can be managed over a certain time horizon. The proposed optimization method is based on a discrete-time model of the overall system in order to represent the shunting operations in the port rail network. The resulting MILP optimization problem has been applied to a real case study referred to the port rail network of La Spezia Container Terminal, in Northern Italy. What-if analyses have been carried out to test the system potentiality by varying some parameters, i.e. the terminal equipment productivity, the number of locomotives and the time to perform some technical operations.